Response of maize grain and stover yields to tillage and different soil fertility management practices in the Semi-Deciduous Forest Zone of Ghana - Amegashie, Kofi Bright (2015)
A thesis presented to the Department of Crop and Soil Sciences, Faculty of Agriculture, College of Agriculture and Natural Resources, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana in partial fulfilment of the requirements for the award of the degree of Doctor of Philosophy in Soil Science